DETERMINAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar dalam Bursa Efek Indonesia) - Dyah Sawitri, 10.05.52.0146; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2014)
This research purpose of was to analyze the factors that affect the disclosure of corporate social responsibility (CSR) in annual report of manufacturing companies listed in Indonesian Stock Exchange (IDX). CSR needsÂ to be disclosed as to analysing the impact on the surrounding environment companies.Samples of this research are manufacturing companies listed in IDX 2010 - 2012. Total sample study for three years of observation is 205 samples. Measurement of corporate social responsibility is based on Corporate SocialÂ Responsibility Index (CSRI) is seem from the companyâs annual report. Analysis tool used multiple linear regression method.The result of this study indicated that the size of the board of commissioners a significant effect on the disclosure of CSR in Indonesian. Mean while, profitability and leverage no significant impact on disclosure of CSR inÂ Indonesia.Keywords: Corporate Social Responsibility (CSR), the size of the board of commissioners, profitability, and leverage